Sociolinguistic and Linguistic Differences between Juray and Sora. - Gomango, O.; Anderson, G.D.S. (The Third International Conference on Linguistics in Sri Lanka, ICLSL 2017. Department of Linguistics, University of Kelaniya, Sri Lanka., 2017)
Living Tongues Institute for Endangered Languages & Berhampur University, India Juray is a seriously endangered Munda language of the Sora-Juray cluster spoken in Gajapati district, southern Odisha State, India (Gomango 2015) by under 25,000, but it is often heavily mixed with Oḍia or with higher valued Sora dialects. Juray remains an unwritten language and is known mainly from a very brief text and a PhD dissertation (Zide 1983, 1982). Juray shows phonological, lexical and morphosyntactic differences from Sora. Thus, we find correspondences in cognate lexemes of /i/ in Sora but /a/ in Juray (1), or in „bee‟ (2), cognate roots in different structural configurations. In other cases, the Sora form appears to have undergone metathesis while Juray reflects the original order (3), or in „wet‟ (4) we find stem reduplication in Juray (and –d-) but a compound form in Sora (with -ɟ-) while in „ear‟ (5), Sora uses the infixed glottal stop but Juray prefixation of /əə-/ from a cognate root. Of course, a number of lexemes are entirely unrelated when comparing Sora with Juray (6). In Juray, the objective case marker always appears after the noun it governs, whether it is a pronominal (7) or a nominal object NP (8), while in Sora the case marker precedes pronouns. Endangered Juray has started to undergo a range of structural changes effecting its lexicon and morphosyntax. Some of these features discussed in this presentation (the position of the object marker) probably reflect processes of accommodation. Others of note we will discuss include the position of certain verbal operators, and the use of plural markers in quantified NPs, none of which are typically found in the less endangered lects of the Sora-Juray cluster. Unless otherwise marked, all data come from the authors‟ field notes. (1) Sora Juray English -əən əə-lib əə-lab-əən „deer‟ id-l-ai ad-l-ai „I have cut it‟ (2) əə-daŋ-bud əə-juŋ-daŋ „bee‟ (3) əə-deba-məər əə-buda-mar „elder man‟ (4) əəɟa-meŋ əəda-əəda „wet‟ (5) luʔud əə-lud „ear‟ (6) anəəpsui əəkengoʔ „toward‟ əədakul səəŋne „rice water‟ (7) Juray (8) Juray əəɟi- ɲen=adoʔŋ giɟ-t-iɲ ɲen ud=an manran=adoʔŋ tij-l-ai mar-an tuɖ woman-N.SFX I-OBJ see-NPST-1UND I basket-N.SFX man-N.SFX-OBJ give-PST-1ACT „the woman sees me‟ „I gave the basket to the man‟
Keywords: Juray; Sora; Dialect; India; Endangered Language